A new spider fly (Diptera: Acroceridae: Ogcodinae: Ogcodes Latreille) from Chiloé Island’s evergreen forest and new distributional records for other spider flies in Chile - Barahona-Segovia, Rodrigo M.; Guzmán, Vicente Valdés; Barceló, Matías; Pañinao-Monsálvez, Laura (Zootaxa, 2020)
Ogcodes Latreille is the largest genus of Acroceridae. They exhibit a cosmopolitan distribution and parasitize several spider families. Eleven Neotropical species are currently recognized in the genus, with five of them occurring in Chile, though distribution data is limited in this group of rarely collected flies. In this work, we describe a new species, Ogcodes kunkunche sp. nov. Barahona-Segovia from the evergreen forest of Chiloé Island, provide an identification key to the Chilean species of Ogcodes, and include novel distributional data for other species of spider flies (Acrocerinae and Ogcodinae). Based in our results, we suggest that O. kunkunche sp. nov. must be incorporated in the porteri group, due to wing vein reduction. Morphological aspects within Ogcodes, and their evolutionary implications are discussed.